Lost Green Chemistries: History of Forgotten Environmental Trajectories. - Krasnodębski, Marcin (Centaurus: Journal of the European Society for the History of Science, 2022)
Green chemistry is a successful new paradigm reshaping the way we think about sustainable chemical synthesis. And yet, its official story, placing the birth of green chemistry in the 1990s within the walls of the Environmental Protection Agency (EPA), is riddled with contradictions and simplifications. Beneath the mainstream narrative, there is another, somewhat forgotten history of numerous attempts to respond to environmental challenges in chemistry with different frameworks and conceptualisations. The frontiers of the concept were far from clear and multiple green chemistries struggled for recognition, both within and beyond the US, with a tremendous amount of theoretical reflection on how to combine sustainability with chemistry conducted in Europe. In Italy, France, and Germany, many scholars anticipated what would become green chemistry in parallel to their American colleagues. And yet, even though the American success story dominated the imaginary of chemists all over the world, these forgotten green-chemistry frameworks developed in the 1990s, be they American or European, present a number of distinct, original features that set them apart. They were not merely imperfect forerunners to a more mature EPA-based concept, but in fact constituted full-fledged alternatives, many of which have a lot to offer to modern practitioners of green chemistry who are unsatisfied with the way the field has evolved. This article tries to recover this forgotten past and to highlight those features that can contribute to contemporary debates on the place of sustainability in chemistry.